The role of top-predator in the preservation of coral reefs ecosystem - Ratianingsih, Rina; Ismawati, Nurul; Puspita, Juni Wijayanti; Jaya, Agus Indra (Indonesian Bio-Mathematical Society, 2017)
The coral reef ecosystem in Indonesian as part of Coral Triangle Region has been significantly decreasing in the last decades. This damage has been known widely due to coastal development, pollution, and uncontrolled fishing and harvesting. Among other many living species in the environment, the existence of coral reefs is directly related to the existence of Drupella sp. and Acanthaster planci as the coral predators, while the existence of the predators also related to the Napoleon wrasse and Giant triton/ Trumpet shell as the top predator. This study discusses the interaction among the coral reefs, the predators and the top predators, which is represented in a dynamical model of predator-prey-top predator. In the absence of top predators, the system is reduced as a two-predator-prey model with only one surviving predator, Acanthaster planci, which has more effective predation behavior. The role of Napoleon wrasse as a top predator of both Acanthaster planci and Drupella sp. is significantly important to protect the coral reef from the excessive predation from Acanthaster planci and Drupella sp. A stable co-existence is shown between coral reef, Acanthaster planci and Napoleon wrasse. With the appearance of Giant tritons which predate only Acanthaster planci, a co-existence between five species may occur with abundant species of Giant triton.